CSF chitinase proteins in amyotrophic lateral sclerosis - Thompson, A; Gray, E; Bampton, A; Raciborska, D; Talbot, K; Turner, M (BMJ Publishing Group, 2019)
Objective: To evaluate the classifier performance, clinical and biochemical correlations of cerebrospinal fluid (CSF) levels of the chitinase proteins Chitotriosidase-1 (CHIT1), Chitinase-3-like protein 1 (CHI3L1) and Chitinase-3-like protein 2 (CHI3L2) in amyotrophic lateral sclerosis (ALS). Methods: CSF levels of CHIT1, CHI3L1, CHI3L2, phosphorylated neurofilament heavy chain (pNFH) and C-reactive protein were measured by ELISA in a longitudinal cohort of patients with ALS (n=82), primary lateral sclerosis (PLS, n=10), ALS-mimic conditions (n=12), healthy controls (n=25) and asymptomatic carriers of ALS-causing genetic mutations (AGC; n=5). Results: CSF CHIT1, CHI3L1 and CHI3L2 were elevated in patients with ALS compared with healthy controls (p<0.001) and ALS-mimics (CHIT1, p<0.001; CHI3L1, p=0.017; CHI3L2, p<0.001). CHIT1 and CHI3L2 were elevated in ALS compared with PLS (CHIT1, p=0.021; CHI3L1, p=0.417; CHI3L2, p<0.001). Chitinase levels were similar in AGCs and healthy controls. Chitinase proteins distinguished ALS from healthy controls (area under the curve (AUC): CHIT1 0.92; CHI3L1 0.80; CHI3L2 0.90), mimics (AUC: CHIT1 0.84; CHI3L1 0.73; CHI3L2 0.88) and, to a lesser extent, PLS (AUC: CHIT 0.73; CHI3L1 0.51; CHI3L2 0.82) but did not outperform pNFH. CHIT1 and CHI3L2 correlated with disease progression rate (Pearson’s r=0.49, p<0.001; r=0.42, p<0.001, respectively). CHI3L1 correlated with degree of cognitive dysfunction (r=−0.25, p=0.038). All chitinases correlated with pNFH. CHIT1 levels were associated with survival in multivariate models. Chitinase levels were longitudinally stable. Conclusions: CSF chitinase proteins may have limited value as independent diagnostic and stratification biomarkers in ALS, but offer a window into non-autonomous mechanisms of motor neuronal loss in ALS, specifically in assessing response to therapies targeting neuroinflammatory pathways.